Manual de funcionamiento, mantenimiento y aplicación pedagógica de equipo (Balanza digital gramera BPS 51 PLUS) en al Laboratorio de Investigación de Lácteos en la carrera de Agroindustria en la Universidad Técnica de Cotopaxi. - Gancino Masabanda, Odalis Maritza (2022)
The Agroindustry Career of the Technical University of Cotopaxi, studies the resources of engineering focused on the transformation of raw materials to obtain a product with an added cost, so it is essential to have the necessary equipment and machinery for the transformation of these raw materials. At present, the Agroindustry career has equipment that has an industrial level capacity, so its use is not totally suitable for the pedagogical process, so it is of utmost importance to have equipment and machinery with didactic capacity. The objective of this work is the elaboration of an operation and maintenance manual, with pedagogical application of the BPS 51 plus digital weighing scale in the Dairy Research Laboratory, with the purpose of having a good handling of the equipment, making the students carry out practices in a reliable way, thus taking the theoretical to the practical. Thus, it was necessary to carry out a bibliographic research, which allowed to know the theoretical foundations necessary for the elaboration and execution of the project. On the other hand, it is worth mentioning that for the elaboration of this work a non-experimental research design was used with three types of research, which are documentary, descriptive and explanatory; as well as the inductive and deductive method was used, and finally, the research techniques used were observation and scientific reading, all this with the purpose of carrying out the project in an adequate way. The operation manual consists of the technical description of the equipment, its functions and how to apply them, the requirements for the proper functioning of the scale, parts of the equipment and the configuration mode. On the other hand, the maintenance manual consists of the different types of maintenance to be applied to the equipment, as well as the precautions to be taken when handling the balance. To demonstrate the proper operation and correct use of the equipment, a practical demonstration was carried out, in which blackberry yogurt was made using the BPS 51 plus digital gram scale in the weighing of the different inputs, thus demonstrating that the scale is very useful in the agroindustry, since thanks to it is possible to place the exact amount of inputs in the production of different agroindustrial products.